Synthesis and tripanocidal activity of ferrocenyl and benzyl diamines against Trypanosoma brucei and Trypanosoma cruzi - Arenas Velasquez, Angela Maria [UNESP]; Francisco, Acacio Ivo; Nakaima Kohatsu, Andrea Akiko [UNESP]; Jesus Silva, Flavia Alves de [UNESP]; Rodrigues, Danilo Fernando [UNESP]; Silva Teixeira, Rafaela Gomes da; Chiari, Bruna Galdorfini [UNESP]; Jose de Almeida, Maria Gabriela [UNESP]; Isaac, Vera Lucia Borges [UNESP]; Vargas, Maria D.; Cicarelli, Regina Maria Barretto [UNESP] (Elsevier B.V., 2014)
Trypanosoma brucei and Trypanosoma cruzi are the etiologic agents of sleeping sickness and Chagas disease, respectively, two of the 17 preventable tropical infectious diseases (NTD) which have been neglected by governments and organizations working in the health sector, as well as pharmaceutical industries. High toxicity and resistance are problems of the conventional drugs employed against trypanosomiasis, hence the need for the development of new drugs with trypanocidal activity. In this work we have evaluated the trypanocidal activity of a series of N1, N2-dibenzylethane-1,2-diamine hydrochlorides (benzyl diamines) and N1-benzyl, N2-methyferrocenylethane-1,2-diamine hydrochlorides (ferrocenyl diamines) against T. brucei and T. cruzi parasite strains. We show that incorporation of the ferrocenyl group into the benzyl diamines increases the trypanocidal activity. The molecules exhibit potential trypanocidal activity in vitro against all parasite strains. Cytotoxicity assay was also carried out to evaluate the toxicity in HepG2 cells. (c) 2014 Elsevier Ltd. All rights reserved.
Keywords: Sleeping sickness; Chagas disease; Benzyl diamines; Ferrocenyl diamines